Pengaruh Biaya dan Harga Terhadap Pendapatan Nelayan di Desa Sampulungan Kecamatan Galesong Utara Kabupaten Takalar - Fitriani, Fitriani Fitri (Universitas Teuku Umar, 2025)
The results of the research show that: (1) the costvariable (X1) has a positive but insignificant effect on the income of fishermen (Y) in Sampulungan village, Galesong Utara district, Takalar regency. This is evidenced by the data processing results where the coefficient of the variable is 0.103 with a significance value of 0.0679, which is greater than 0.05, and the calculated t value of 0.417 is smaller than the table t value of 2.026. (2) the price variable (X2) has a positive but insignificant effect on the income of fishermen (Y) in Sampulungan village, Galesong Utara district, Takalar regency. This is evidenced by the data processing results where the coefficient of the variable is 0.054 with a significance value of 0.877, which is greater than 0.05, and the calculated t value of 0.155 is smaller than the table t value of 2.026.Keywords: Cost, Price, and Income